2015
DOI: 10.1001/jamasurg.2014.3848
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Long-term Effectiveness of the WHO Surgical Safety Checklist Combined With Pulse Oximetry in a Resource-Limited Setting

Abstract: Sustained use of the checklist was observed with continued improvements in process measures and reductions in 30-day surgical complications almost 2 years after a structured implementation effort that demonstrated marked, short-term reductions in harm. The sustained effect occurred despite the absence of continued oversight by the research team, indicating the important role that local leadership and local champions play in the success of quality improvement initiatives, especially in resource-limited settings. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
(31 reference statements)
0
52
0
2
Order By: Relevance
“…In addition, we report a 40% decreased odds of occurrence of ≥ 1 surgical complication with use of an SSC compared with no surgical checklist with adjustment for presence of an observer, ASA score, and anesthesia time. In many reports of human medicine studies, the success of implementation of an SSC in decreasing both postoperative complications and mortality rates has been documented . To the best of the authors' knowledge, only 1 study in the veterinary literature has documented the benefits of an SSC for decreasing complications, but with no documentation regarding mortality .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we report a 40% decreased odds of occurrence of ≥ 1 surgical complication with use of an SSC compared with no surgical checklist with adjustment for presence of an observer, ASA score, and anesthesia time. In many reports of human medicine studies, the success of implementation of an SSC in decreasing both postoperative complications and mortality rates has been documented . To the best of the authors' knowledge, only 1 study in the veterinary literature has documented the benefits of an SSC for decreasing complications, but with no documentation regarding mortality .…”
Section: Discussionmentioning
confidence: 99%
“…The SSC consists of a series of inquiries or assurances designed to confirm patient identity prior to anesthetic induction, before an incision is made, and prior to the patient leaving the operating room (OR) . Since implementation of the WHO SSC, there have been multiple reports of improved detection of safety hazards, decreased overall surgical complication rates and in‐hospital mortality, and improved communication between OR personnel . The report of one of the original prospective studies on implementing the WHO SSC across 8 hospitals worldwide concluded that the rate of surgical complications at all sites dropped from 11.0% to 7.0% after introduction of the checklist, and the total in‐hospital rate of death dropped from 1.5% to 0.8% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With persistence and collective leadership from hospital administration as well as surgical, nursing, and anesthetic disciplines, long-term and sustainable improvements in practice can be maintained. 13 The World Health Assembly (WHA), the highest body to set health policy and responsible for governing the World Health Organization (WHO), recently passed resolution WHA68.15, ''Strengthening Essential and Emergency Surgery and Anesthesia Care as a Component of Universal Health Coverage''. 14 This is the first global recognition of anesthesia as essential for improving perioperative outcomes and should empower the WHO to push for improvements in these more complex aspects of care delivery.…”
mentioning
confidence: 99%
“…Avec de la persévérance et le leadership collectif de l'administration hospitalière,et des disciplines de chirurgie, de soins infirmiers et d'anesthésiologie, des améliorations durables et à long terme des pratiques peuvent être maintenues. 13 L'Assemblée mondiale de la santé (AMS), l'organisation la plus haut placée pour l'établissement des politiques et responsable du fonctionnement de l'Organisation mondiale de la santé (OMS), a récemment passé la résolution WHA68,15, « renforçant la place des soins chirurgicaux et anesthésiques essentiels et urgents comme éléments de la couverture de santé universelle ». 14 Il s'agit de la première reconnaissance internationale du caractère essentiel de l'anesthésie pour l'amélioration des résultats péri-opératoires et elle doit donner à l'OMS la force d'insister sur les améliorations à apporter à ces aspects plus complexes des soins.…”
unclassified